Pembuatan Video Panduan Layanan Perpustakaan di Perpustakaan Universitas Andalas - Gesti, Elga Kamara; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract This paper discusses the making of the library services guide video at library of Andalas University. The purpose of this paper is to describe the making of library service guide video in the library of Andalas University to make it easier tofind an information needed. The method used is qualitative method of interview and observation. There are three stages in the video production: first, preproduction is an early stage before the implementation of video production. This step are very important for video production because this stage is all the planning steps for video production is done. In this preproduction stage was done: search and discovery of ideas, making synopsis, treatment, storyboard, shooting script, production planning, and production preparation. Second, Production, video production stage is the stage to realize all the steps that exist in preproduction stage. At the production stage, the video production team is usually led by director who has a role to take responsbility for ongoing running of video production. Usually the director assisted by several assistants to assist in ongoing video production. Third, postproduction is the final stage in video production before the video is ready to be presented or distributed. In this postproduction process were required video editing software and adequate tools to perform video editing process.Keywords: video, guide, library